ANALYSIS OF ERRORS IN SOLVING FUNCTION PROBLEMS IN EIGHT GRADE STUDENTS’ OF SMP MUHAMMADIYAH 2 GODEAN - Ika Wahyu Ningrum; Edi Prajitno (Universitas Ahmad Dahlan, 2017)
Students often make mistakes in solving problems are the function of misconceptions, miscalculations and errors procedure. That's because students do not have the ability to understand the concepts, capabilities in the calculation and the ability to understand the procedure better. This research aims to determine the percentage of types of misconceptions, miscalculations, and procedural errors function procedure eighth-grade students of SMP Muhammadiyah 2 Godean the academic year of 2016/2017. The research was conducted at SMP Muhammadiyah 2 Godean in class VIII C that all students totaling 32. The selection of research subjects taken on the recommendation of teachers, selected class VIII C because this class has an average mathematics achievement is low. Data collection techniques in this research using the test method and the interview method. The instrument used was a problem in narrative form as much as 6 questions and interview guides students. The data analysis technique used is descriptive qualitative analysis techniques to identify each type of mistakes made by the students. The results show the average percentage of misconceptions made by students of 82,292% (very high), the percentage of miscalculations made by the students of 42,708% (medium), and the percentage of procedural errors made by the students of 67,708% (high ). Mistakes made by students of class VIII C SMP Muhammadiyah 2 Godean relatively the same: there is no answer, wrong in understanding and translating the question, in applying the formula to resolve the matter, one to operate the calculations, one in determining the final outcome, not coherently in writing step completion, incomplete in writing steps to resolve and does not use logical reasoning to draw conclusions